(untitled) (Research, Society and Development, 2021)
Objective: To analyze the impact of family relationships on suicidal behavior. Methodology: Exploratory, descriptive research, qualitative approach, carried out from December 2017 to November 2019 in the Emergency Care Unit of Assis / SP. Interviews conducted with people attempting suicide. Content Analysis methodological framework was used. Research project approved by the Research Ethics Committee. Results: Interviewed 113 participants out of a total of 309 occurrences of attempted suicide identified in the period. The majority were female 86 (76.1%), between 18 and 30 years old 57 (50.4%), heterosexual 103 (91.2%), self-declared white skin color 62 (54.9%), single 49 (43.4%), high school completed 41 (43,2%). without physical pathology 70 (61.9%), with mental disorder 70 (61.9%), without drug use 74 (65.5%). As a protective factor, family relationships and the family model are characterized by family attachment, with feelings of love and respect, and with effective support from the family. At the other end, as a risk factor, negative family relationships erupt in fights, family violence, a sense of non-belonging and betrayal. Final considerations: The family has the potential to generate a positive impact when it presents support and sentimental attachment among its members, but maladjusted family relationships have a negative impact and become a risk factor for suicidal behavior.